Cardiac Dysfunction Biomarkers Are Associated With Potential for Successful Separation From Extracorporeal Membrane Oxygenation in Children. Issue 2 (10th May 2022) - Coletti, Kristen; Griffiths, Megan; Nies, Melanie; Brandal, Stephanie; Everett, Allen D.; Bembea, Melania M.
Abstract : Biomarkers of cardiac dysfunction may aid in decision making about organ recovery and optimal timing of separation from extracorporeal membrane oxygenation (ECMO). We conducted a prospective observational study of children from 0 to <18 years who underwent ECMO between 7/2010 and 6/2015 in a single center. In this pilot study, we aimed to determine whether Suppression of tumorigenicity 2 (ST2), N -terminal pro–B-type natriuretic peptide (NT-proBNP), galectin-3, and endostatin were associated with ability to separate from ECMO. Fifty neonatal and pediatric participants supported on venoarterial ECMO were included (median age 13 days, 50% male). Twelve (24%) participants were unable to separate from extracorporeal support. Plasma ST2 concentrations at cannulation were higher in children who were ultimately unable to separate versus those who successfully separated from ECMO (median 395.3 ng/mL vs. 207.4 ng/mL, p = 0.012). ST2 and NT-proBNP concentrations decreased significantly from the first to the last ECMO day in patients successfully separated from ECMO ( p < 0.0001 and p = 0.017, respectively). Endostatin concentrations increased significantly from the first to the last ECMO day in both groups. Galectin-3 concentrations were not associated with the ability to separate from ECMO. Cardiac dysfunction biomarkers, particularly ST2, may aid in decannulation decision-making in pediatric ECMO patients. These results should be validated with a larger study.